INDONESIAN PEASANTS' UNION IN THE STRUGGLE OF AGRARIAN REFORM IN INDONESIA, PERIOD 1998-2011 - Purwanto, Heri; Nasution, Faiz Albar (Journal of Peasants' Rights, 2022)
A This study discusses the struggle for Agrarian Reform carried out by the Indonesian Peasant Union in 2011. The purpose of this study is to explain the strategy of the peasant movement in fighting for agrarian reform in Indonesia. More deeply, this research will describe the strategy of the Indonesian Peasants Union (SPI) in fighting for agrarian reform. This study uses a qualitative approach, and uses a descriptive analytical method to analyze the data obtained. Data collection techniques were carried out through library research, document collection and in-depth interviews with five informants, Synthesis activists, the General Chair and members of the Indonesian Peasant Union, agrarian experts, and CNDS activists. The results of this study indicate that the SPI's agrarian struggle at the local level is carried out by prioritizing the power of the masses to occupy land and carry out mass actions. In 2011, SPI has succeeded in controlling and reclaiming 47,270 hectares of land for farmers, and hasn become productive land that supports and improves the economy of farming families. To garner support at the local level, SPI builds alliances with farmer, labor, fisherman, student and NGO organizations. At the national level, SPI's struggle was aimed at urging the state to implement Law No. 5 of 1960 concerning Basic Agrarian Regulations. The Indonesian Peasant Union's strategy to oppose oppressive power relations was carried out to deal with various forms of power in various spaces and levels.